Effect of Coconut Fiber and Expired Cement on the Physical-Mechanical and Thermal Properties of Adobe Blocks - Hurtado, Russell Jeanpierre Laureano; Vasquez, Sandra Milena Melo; Asto, Doris Martinez; Luna, Manuel Ismael Laurencio (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2026)
Adobe remains an essential construction material for rural housing in the Andean highlands, yet its performance is limited by high water absorption, insufficient durability, and moderate mechanical strength. This study systematically evaluated the effect of combined coconut fiber and expired cement additions on the mechanical, hygrothermal, and economic properties of adobe blocks and walls. Soil was characterized, and blocks were reinforced with coconut fiber (0.6%, 0.9%, 1.2%, 1.5% by weight) and expired cement (3%, 6%, 9%), both by weight of dry soil. A total of 135 samples underwent tests for compressive, tensile, and flexural strength, water absorption, thermal conductivity, and wall compressive performance. Statistical analysis using ANOVA confirmed highly significant improvements (p < 0.0001) across all evaluated properties. The optimal mixture, comprising 0.9% coconut fiber and 9% expired cement, achieved a compressive strength of 37.86 kg.cm-2, nearly double that of the control sample (adobe without additives), which reached 17.69 kg.cm-2, while wall compressive strength reached 33.9 kg.cm-2. Tensile and flexural strengths increased to 11.43 kg.cm-2 and 19.78 kg.cm-2, respectively; water absorption decreased to 7.82%, and thermal conductivity was reduced to 0.52 W.m-1.K-1. Economically, the improved adobe presented a unit cost of S/ 154.14 per m2 (Peruvian soles), 27% higher than the control sample, although offset by notable gains in durability and overall performance. In summary, the combined use of coconut fiber and expired cement in adobe yields statistically validated improvements in structural, hygrothermal, and economic behavior, offering a practical and sustainable alternative for resilient rural housing in high altitude regions.